2021
DOI: 10.3390/w13070920
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of River Stage Using Multistep-Ahead Machine Learning Techniques for a Tidal River of Taiwan

Abstract: Time-series prediction of a river stage during typhoons or storms is essential for flood control or flood disaster prevention. Data-driven models using machine learning (ML) techniques have become an attractive and effective approach to modeling and analyzing river stage dynamics. However, relatively new ML techniques, such as the light gradient boosting machine regression (LGBMR), have rarely been applied to predict the river stage in a tidal river. In this study, data-driven ML models were developed under a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In this study, five regression techniques of machine learning are applied to generate data-driven models. The primary process when developing these models is called the "learning phase," where the relationship between the input and output variables of the system is established (Guo et al, 2021):…”
Section: Regression Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, five regression techniques of machine learning are applied to generate data-driven models. The primary process when developing these models is called the "learning phase," where the relationship between the input and output variables of the system is established (Guo et al, 2021):…”
Section: Regression Methodsmentioning
confidence: 99%
“…In this study, five regression techniques of machine learning are applied to generate data‐driven models. The primary process when developing these models is called the “learning phase,” where the relationship between the input and output variables of the system is established (Guo et al, 2021): y=f(x) $y=f(x)$with the available data: [(x1,y1),(x2,y2),(xn,yn)]={xi,yi}i=1n, $[({x}_{1},{y}_{1}),({x}_{2},{y}_{2}),\text{\unicode{x02026}}\,({x}_{n},{y}_{n})]={\{{x}_{i},{y}_{i}\}}_{i=1}^{n},$where x is the input vector, y is the output vector, n is the number of observations and f is the regression function.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…not considering studies in single-step-ahead forecasting. There is one interesting recent study by Guo et al (2021) pointing out that gradient boosting machine, a new type of machine learning algorithm, performs favourably for some step-ahead prediction. This application could be explored in the future.…”
Section: Multi-step-ahead Prediction Using Univariate and Multivariate Lstmmentioning
confidence: 99%
“…The results suggested that the LSTM model is the most accurate in their study area and can be helpful for the development of a flood operational forecasting system. Guo et al (2021) proposed and employed four DD models, namely, SVR, random forest regression (RFR), MLPR, and light gradient boosting machine (LightGBM), to predict the river stage at the tidal reach of the Lan-Yang River Basin, Taiwan. Based on their simulated results with 1-6 h lead times, the LightGBM model achieved the best overall performance among the four tested models.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%